1962
DOI: 10.1002/art.1780050203
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia in a male Filipino population

Abstract: In view of the high frequency of gouty arthritis reported in Filipinos, a population of normal Filipino males and an age‐matched group of Caucasian males were examined. The mean serum uric acid value (with standard deviation) was found to be 6.3 ± 1.4 mg. per 100 ml. for Filipinos and 5.0 ± 1.1 mg. per 100 ml. for Caucasians, using the uricaseultraviolet spectrophotometric method of Praetorius. The serum uric acid frequency distribution curve was found to be symmetrical for the Caucasians and skewed to high va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
1

Year Published

1964
1964
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 13 publications
2
11
0
1
Order By: Relevance
“…The uric acid level of 6.8 mg% is significantly higher than the mean for Caucasians in the United States (5.2 mg%) (1,5 T h e inhabitants of Samoa are Polynesian and are related to other peoples of the central and eastern Pacific, forming a part of the family which includes the Hawaiians, the Tahitians, the Tongans, and the Maoris of New Zealand and Cook Islands. T h e Samoan language is closely related to other Polynesian tongues.…”
Section: Resultsmentioning
confidence: 90%
“…The uric acid level of 6.8 mg% is significantly higher than the mean for Caucasians in the United States (5.2 mg%) (1,5 T h e inhabitants of Samoa are Polynesian and are related to other peoples of the central and eastern Pacific, forming a part of the family which includes the Hawaiians, the Tahitians, the Tongans, and the Maoris of New Zealand and Cook Islands. T h e Samoan language is closely related to other Polynesian tongues.…”
Section: Resultsmentioning
confidence: 90%
“…Kellgren has suggested that the people of the Pacific belong to one large gouty family (1 1). Indeed, high serum uric acid levels have been reported for Maori, Cook Island and Samoan Polynesians (1 2, 13), Filipinos (14,15), Indonesian Malayans (16) (14,15) but not among those in the Philippine Islands (19). Healey et a1 have suggested that this difference may be due to an inherited defect in renal excretion of uric acid which becomes manifest when the Filipinos change to a high purine Western diet (1 9).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies linked the introduction of a Western diet with an increased frequency of hypertension and gout, such as with the Maori Indians or Japanese Americans [27]. The immigration of Filipinos into the United States was also associated with a marked increase in the frequency of gout and hypertension [28].…”
Section: Uric Acid Is Commonly Elevated In Patients With Hypertensionmentioning
confidence: 99%